Molecular Characterization of the Escherichia coli Asymptomatic Bacteriuria Strain 83972: the Taming of a Pathogen - Klemm, Per (American Society for Microbiology, 2006)
Escherichia coli 83972 is a clinical asymptomatia bacteriuric isolate that is able to colonize the human urinary bladder without inducing an immune response. Here we demonstrate that one of the mechanisms by which this strain has become attenuated is through the mutation of its genes encoding type 1 and P fimbriae.